Analysis of reading errors in Portuguese : digraphs and complex syllabic structures - Simões, Edlia; Martins, Margarida Alves (Análise Psicológica, 2020)
Abstract: The Portuguese language poses several challenges for children in the initial phase of learning how to read, particularly in the case of letters that may correspond to more than one phoneme, two letters that correspond to a single phoneme and in the case of words containing complex syllabic structures. The objective of this study was to perform a psycholinguistic analysis of the reading errors of children, attending the 1st (n=175) and 2nd year (n=137) of schooling, specifically in the case of words containing digraphs or complex syllabic structures and to analyse the differences between children’s reading errors in these two years. An oral reading test was used for data collection. A quantitative and qualitative analysis of the type of reading errors was conducted using words with consonant digraphs (ch, nh, lh, gu, rr, ss), and words with complex syllables <CVC and CCV>. This analysis showed that children presented greater difficulties in some specific digraphs and tended to simplify complex syllables, either by adding or deleting phonemes. The quantity and quality of the reading errors of children attending both grades were discussed in light of reading acquisition theories and children’s phonological development.
0 citations (Crossref) [2023-03-15] Accepted: 2021-01-20T11:46:39Z